A pilot study of muscle plasma protein changes after exercise. Issue 2 (30th August 2013) - Dahlqvist, Julia R.; Voss, Line G.; Lauridsen, Thomas; Krag, Thomas O.; Vissing, John
ABSTRACT Introduction: Creatine kinase (CK) and myoglobin (Mb) do not possess all good qualities as biomarkers of skeletal muscle damage. We investigated the utility of troponin I (TnI) and telethonin (Tcap) as markers and examined their temporal profiles after skeletal muscle damage. Methods: Plasma profiles were measured before and after exercise in 3 groups: subjects affected by either Becker muscular dystrophy or McArdle disease, and healthy subjects. Results: Mb and TnI appeared early in the blood, and the increase of TnI was only observed in patients with muscle disease. The CK increase was more delayed in plasma. Tcap was not detectable at any time. Conclusions: Our results suggest that TnI is a marker of more severe damage signifying sarcomeric damage, and it could therefore be an important supplement to CK and Mb in clinical practice. Tcap is not useful as a marker for skeletal muscle damage. Muscle Nerve49: 261–266, 2014